Identification of pyrrolizidine alkaloids and flavonoid glycosides through HR-LCMS/MS analysis, biological screening, DFT and molecular docking studies on Heliotropium dasycarpum Ledeb. - Mahreen Mukhtar; Muhammad Saleem; Mamona Nazir; Naheed Riaz; Nusrat Shafiq; Hammad Saleem; Saba Tauseef; Saima Khan; Muhammad Ehsan Mazhar; Rasool Bakhsh Tareen; Mian Habib ur Rahman Mahmood; Muhammad Imran Tousif; et al. (Arabian Journal of Chemistry, 2023)
The current study was carried out to reveal the chemical profile and biological screening of Heliotropium dasycarpum Ledeb, as well as the feasibility of its industrial application. Therefore, the methanolic extract (HdM) of H. dasycarpum was divided into n-hexane (HdH), ethyl acetate (HdE) and water (HdW) soluble fractions. All the fractions were inactive against acetylcholinesterase (AChE) enzyme, 3T3 and HeLa cell lines, but showed immunomodulatory effect up to 37 %. HdE fraction further displayed significant anti-urease activity with IC50 value of 74.072 ± 0.002, while HdM was found moderate inhibitor (63 %). Thus HdE was subjected to HR-LCMS/MS analysis in positive and negative ionization modes, and a qualitative analytical method with a data mining strategy was utilized. The secondary metabolites were identified by dereplication strategy using molecular networking as a bioinformatics tool, which disclosed the presence of 08 known alkaloids of heliotrine-type (1, 3, 5–10), and 05 (12–16) known flavonoids and flavonoid glycosides along with 03 new (2, 4 and 11) putative pyrrolizidine analogues. DFT simulations of identified compounds were performed using multiple quantum chemical and geometrical descriptors in order to determine their quantitative structure activity relationship. These secondary metabolites were docked against the enzyme urease which substantiated the inhibitory action of pyrrolizidine alkaloids and flavonoid glycosides. Furthermore, ADME analysis provided the base for the use of these compounds for further studies as drug leads and to unveil industrial application of H. dasycarpum in formulating products against gastritis, peptic ulcer and gastric cancer.